Screen use: its association with caregiver mental health, parenting, and children's ADHD symptoms - Waller, F; Prandstetter, K; Jansen, E; Nikolova, G; Lachman, JM; Hutchings, J; Foran, HM (Wiley, 2023)
Objective: The aim was to examine the relationship between caregiver's mental health (parental psychological distress, and parenting stress), dysfunctional parenting (lax or overreactive parenting), and the screen media use in understanding attention-deficit/hyperactivity disorder (ADHD) symptoms of children within an integrated model framework. Background: Familial factors and screen use have shown to be significantly related to ADHD in children. However, theoretical models of the role of family environment, screen use, and ADHD have rarely been tested jointly, and little is known about these associations in southeastern European middle-income countries (MICs). Method: Data from 835 primary caregivers (92% biological mother, 4% biological father, 3% grandmother or grandfather, 1% other) of children (2 to 9 years) from three MICs were analyzed using path analyses, and models were tested for generalizability across education levels and marital status using multigroup analyses. ADHD-related symptoms were assessed with a structured clinical interview (Mini International Neuropsychiatric Interview for Children and Adolescents–Parent Version [MINI-KID-P]) and the Child Behavioral Checklist (CBCL). Results: Whereas screen use was directly associated with ADHD symptoms across measures, a significant indirect effect of lax parenting on attentional problems via screen use was found only for the CBCL parent report. The final models were tested using multigroup analyses across education levels and marital status with no significant differences. Conclusion: Investments in resource and capacity building for children's primary caregivers that target lax parenting and limiting of screen use may impact children's attentional problems across educational levels and married and nonmarried caregivers.